Chronic Granulomatous Disease Mimicking Colonic Crohn's Disease Successfully Treated with Infliximab. Issue 1 (2017) - Peixoto, Armando; Coelho, Rosa; Maia, Tiago; Sarmento, António; Magro, Fernando; Macedo, Guilherme
ABSTRACT : N/A: Chronic granulomatous disease (CGD) is a genetically induced disease caused by mutations in one of the components of the NADPH‐oxidase in phagocytes, characterized by life‐threatening bacterial and fungal infections and granuloma formation. Treatment includes prevention of infectious complications and immunomodulation. However, a standard strategy is not yet defined. The authors report an X‐linked CGD female carrier who presented during adulthood with diarrhea and colorectal ulcers, with high impairment of quality of life. Induction with infliximab 5 mg/kg (weeks 0, 2, and 6) with infectious prophylaxis was initiated. She continued infliximab 5 mg/kg every 8 weeks with complete symptomatic response at 15 months.